H2S Donor, S-Propargyl-Cysteine, Increases CSE in SGC-7901 and Cancer-Induced Mice: Evidence for a Novel Anti-Cancer Effect of Endogenous H2S? - MA, Kaium; Liu, Yan; Zhu, Qing; Liu, Chun-hua; Duan, Jun-Li; Tan, Benny K-H.; Zhu, Yi Zhun (PLOS ONE, 2011)
Background S-propargyl-cysteine (SPRC), an H2S donor, is a structural analogue of S-allycysteine (SAC). It was investigated for its potential anti-cancer effect on SGC-7901 gastric cancer cells and the possible mechanisms that may be involved. Methods and Findings SPRC treatment significantly decreased cell viability, suppressed the proliferation and migration of SPRC-7901 gastric cancer cells, was pro-apoptotic as well as caused cell cycle arrest at the G1/S phase. In an in vivo study, intra-peritoneal injection of 50 mg/kg and 100 mg/kg of SPRC significantly reduced tumor weights and tumor volumes of gastric cancer implants in nude mice, with a tumor growth inhibition rate of 40–75%. SPRC also induced a pro-apoptotic effect in cancer tissues and elevated the expressions of p53 and Bax in tumors and cells. SPRC treatment also increased protein expression of cystathione-γ-lyase (CSE) in cells and tumors, and elevated H2S levels in cell culture media, plasma and tumoral CSE activity of gastric cancer-induced nude mice by 2, 2.3 and 1.4 fold, respectively. Most of the anti-cancer functions of SPRC on cells and tumors were significantly suppressed by PAG, an inhibitor of CSE activity. Conclusions Taken together, the results of our study provide insights into a novel anti-cancer effect of H2S as well as of SPRC on gastric cancer through inducing the activity of a new target, CSE.